2009
DOI: 10.1099/vir.0.006486-0
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus infection downregulates the expression of glial fibrillary acidic protein in human glioblastoma U373MG cells: identification of viral genes and protein domains involved

Abstract: Human cytomegalovirus (HCMV) has tropism for glial cells, among many other cell types. It was reported previously that the stable expression of HCMV immediate-early protein 1 (IE1) could dramatically reduce the RNA level of glial fibrillary acidic protein (GFAP), an astroglial cell-specific intermediate filament protein, which is progressively lost with an increase in glioma malignancy. To understand this phenomenon in the context of virus infection, a human glioblastoma cell line, U373MG, was infected with HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…We predict that many more of the genes repressed by IE1 than those listed in Table 1 and marked as STAT3-responsive in Table 2 will turn out to be activated by signaling via pSTAT3. Although, to our knowledge, this is the first systematic genome-wide analysis of transcriptional repression by IE1, our results are consistent with earlier findings linking the viral protein to down-regulation of the genes encoding glial fibrillary acidic protein [ 77 , 78 ] and SOCS3 [ 30 ], both of which are activated by pSTAT3 [ 79 82 ]. Our results are also in line with previous reports on inhibition of IL6 signaling by hCMV, although hCMV-dependent activation of IL6 signaling has also been observed [ 30 , 83 ].…”
Section: Discussionsupporting
confidence: 92%
“…We predict that many more of the genes repressed by IE1 than those listed in Table 1 and marked as STAT3-responsive in Table 2 will turn out to be activated by signaling via pSTAT3. Although, to our knowledge, this is the first systematic genome-wide analysis of transcriptional repression by IE1, our results are consistent with earlier findings linking the viral protein to down-regulation of the genes encoding glial fibrillary acidic protein [ 77 , 78 ] and SOCS3 [ 30 ], both of which are activated by pSTAT3 [ 79 82 ]. Our results are also in line with previous reports on inhibition of IL6 signaling by hCMV, although hCMV-dependent activation of IL6 signaling has also been observed [ 30 , 83 ].…”
Section: Discussionsupporting
confidence: 92%
“…IE1 may accomplish transcriptional activation via interactions with a diverse set of cellular transcription regulatory proteins thereby acting through multiple DNA elements [50], [51], [52], [54], [55], [56], [57], [58], [59], [105], [106], [109], [110], [111], [112], [113], [117], [118], [119], [120], [121], [122], [123], [124], [125], [126] as well as epigenetic mechanisms including histone acetylation [53], [59], [127]. More recently, IE1 has also been implicated in transcriptional repression [31], [32], [33], [57], [62], [63], [64]. Our own work ([31] and this study, Figure 4 B) and a report by Huh et al (2008) has demonstrated that IE1 can inhibit the hCMV- or IFN-α/β-dependent activation of human ISGs including ISG54, MxA, PKR, and CXCL10.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, IE1 stimulates expression from a broad range of viral and cellular promoters in transient transfection assays. However, IE1-mediated activation or repression of merely a few single endogenous human genes has been demonstrated so far [58], [59], [60], [61], [62], [63], [64].…”
Section: Introductionmentioning
confidence: 99%
“…For example, IE1 up-regulates the transcription of interleukin 6 (IL-6) and the genes activated by signal transducer and activator of transcription 1 (STAT1) [ 36 ]. Moreover, IE1 inhibits transactivation of p53-dependent downstream genes, disrupts transcription of STAT3-activated genes, and downregulates certain essential NPC markers such as the glial fibrillary acidic protein (GFAP) [ 37 40 ].…”
Section: Introductionmentioning
confidence: 99%